Mediating effects of stalking victimization on gender differences in mental health - Kühner, Christine; Gass, Peter; Dreßing, Harald (Journal of interpersonal violence, 2012)
Studies suggest that stalking victimization may have a serious mental health impact. The present article investigates gender differences in mental health and possible mediating effects of stalking victimization in a community sample. The study includes a postal survey of 665 German community residents on the experience of stalking and various mental health indicators. In a majority of mental health scales, women score poorer than men, and a higher percentage of women fulfill criteria for a current mental disorder and used psychotropic medication. However, effects of gender decrease to a nonsignificant level when stalking victimization is entered into the respective models. Furthermore, associations of stalking victimization with poor mental health, psychosocial functioning, and use of medication are largely comparable across gender.